Validity and Reliability of a New Tool to Evaluate Impaired Airway Clearance in Hospitalized Pediatric Subjects With Respiratory Distress - Shutes, Brittany L; Evans, Laura R; Moore-Clingenpeel, Melissa D; Karsies, Todd J (Respiratory care, 2019)
Chest physiotherapy has been reported to be beneficial in specific clinical contexts, yet it carries a risk of potential serious adverse events with little benefit in other patients. Therefore, identifying and limiting airway clearance therapies to patients with the greatest potential benefit and least risk is clinically relevant and important. This study aims to validate the Airway Clearance and Expansion Index (ACE-I) for the serial assessment of hospitalized pediatric patients with impaired airway clearance and to establish reliability in score acquisition across a range of pediatric respiratory disease states. Content validity of the category importance and category choices was assessed via a survey of well-established pediatric pulmonary and critical care physicians, as well as respiratory therapists (RTs). Inter-rater reliability testing was performed on hospitalized children from October 2016 through April 2017 and analyzed using a one-way random effects intraclass correlation. 51 providers (24 of 37 physicians and 27 of 92 RTs) responded to the survey. Agreement was defined as any score of 6 or greater out of 10 on a scale of 1-10. The total ACE-I scale content validity index (S-CVI) scores for category importance and category choices for physicians were 1 and 0.75, respectively, and for RTs the scores were 0.75 and 0.75, respectively. 172 subjects were scored by multiple raters, resulting in an excellent overall intraclass correlation coefficient of 0.77 (95% CI 0.71-0.83) and the following component scores: cough, 0.72 (95% CI 0.64-0.79); breath sounds, 0.54 (95% CI 0.43-0.64); chest radiograph findings, 0.84 (95% CI 0.79-0.88); and secretions 0.85, (95% CI 0.81-0.89). The ACE-I score addresses and quantifies 4 components of the respiratory assessment that RTs and pediatric physicians deem important in identifying patients who have impaired airway clearance and might benefit from airway clearance and expansion therapies. In addition, the ACE-I score had excellent inter-rater reliability and clinical feasibility within our single institution.